Targeted (PCR‐based) screening of antibiotic resistance genes' prevalence in the gut microbiota of tribal people of Nabarangpur, Odisha, India. (15th January 2022) - Sethi, M.; Mohanty, V.; Mishra, S.; Dash, J.; Mahapatra, S.; Parida, D.; Mohapatra, A.P.; Mishra, R.; Prasad, P.; Parida, A.; Senapati, S.
Abstract: Antibiotic resistance is a major public health concern worldwide. The gut microbiota harbours multiple antibiotic resistant genes (ARGs) that contribute to the existing and future microbial population in a community or ecosystem. This study aimed to investigate the prevalence of 35 antibiotic resistance genes (ARGs) in the gut microbiota of the tribal people of Nabarangpur, Odisha, India. A total of 83 faecal samples were collected from three different tribes (Bhatra, Gond, and Paraja). Total faecal DNA was extracted, and the simplex polymerase chain reaction was performed to detect selected ARGs. Further analysis was done to estimate the incidence of these ARGs across these tribes based on alcohol consumption habits. We identified a higher prevalence of tetracycline resistance genes ( tetW, tetQ and tetM ) in the gut microbiota among three populations. Furthermore, a significant ( P  = 0·024) difference in ARG prevalence against vancomycin in individuals with and without alcohol consumption habits was noticed. The overall distribution of ARGs among the three major tribes of this location was found to be very similar. Together, irrespective of the tribes, the people of this location have gut microbiota harbouring different kinds of ARGs and tetracycline‐resistant genes are the most commonly found ARGs. Abstract : Significance and Impact of the Study: This is the first attempt to check the prevalence of different ARGs in the gut microbiota of tribal people of Nabarangpur, Odisha, which is a small contributing step in controlling the evolving antibiotic resistance in India. The results of this study showed the dominance of tetracycline resistance genes ( tetW, tetQ and tetM ) as well as the similar pattern of distribution of ARGs among the three major tribes of this location. These findings provide a reference to monitor the evolution of antimicrobial resistome in this population in the future.